1983
DOI: 10.2307/280454
|View full text |Cite
|
Sign up to set email alerts
|

Precise Characterization of Guatemalan Obsidian Sources, and Source Determination of Artifacts from Quiriguá

Abstract: For the determination of provenience of obsidian artifacts, precise and accurate measurements of composition patterns of the geologic sources are necessary for definitive and cost-effective assignments. Inter-comparison of data from different laboratories is often difficult. Suggestions for maximizing the usefulness of data already in the literature are made, contributions to a useful data bank of source composition patterns are recorded, and provenience determinations of 30 artifacts excavated in Quirigua, Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 11 publications
2
47
0
3
Order By: Relevance
“…Most of these studies have utilized sophisticated procedures such as neutron activation analysis or X-ray fluorescence to "finger print" primary outcrops of igneous rocks such as obsidian or vitrophyre (Stevenson and McCurry, 1990;Nelson, 1984;Nelson and Holmes, 1979;Jack and Heizer, 1968;Shelley et al, 1988). Such studies have provided substantial amounts of information useful to studying exchange and possible prehistoric movement patterns (Hughes, 1986;Stross et al, 1983;Griffin et al, 1969). However, such studies have not been demonstrated as useful in characterizing nonigneous rocks nor do they provide a means for assessing the variability of secondary deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have utilized sophisticated procedures such as neutron activation analysis or X-ray fluorescence to "finger print" primary outcrops of igneous rocks such as obsidian or vitrophyre (Stevenson and McCurry, 1990;Nelson, 1984;Nelson and Holmes, 1979;Jack and Heizer, 1968;Shelley et al, 1988). Such studies have provided substantial amounts of information useful to studying exchange and possible prehistoric movement patterns (Hughes, 1986;Stross et al, 1983;Griffin et al, 1969). However, such studies have not been demonstrated as useful in characterizing nonigneous rocks nor do they provide a means for assessing the variability of secondary deposits.…”
Section: Introductionmentioning
confidence: 99%
“…Since the mid-1960s, a variety of analytical chemistry techniques have been used to characterize obsidian sources and artifacts for provenance research (4,(32)(33)(34)(35)(36). The most common of these methods include optical emission spectroscopy (OES), atomic absorption spectroscopy (AAS), particle-induced Xray emission spectroscopy (PIXE), inductively coupled plasma-mass spectrometry (ICP-MS), laser ablation-inductively coupled plasma mass spectrometry (LA-ICP-MS), X-ray fluorescence spectroscopy (XRF), and neutron activation analysis (NAA).…”
Section: Methods For Chemical Characterization Of Obsidianmentioning
confidence: 99%
“…Complications and some confusion in nomenclature have arisen from this. For example, Stross et al (1976:245) published XRF results and later (Stross et al 1983) INAA results for obsidian from the Magdalena (subtitled "Santa Teresa") flow. In the 1983 publication they also referred to the "Etzatlan" source as did Ericson and Kimberlin (1977).…”
Section: Source Samplesmentioning
confidence: 96%